Advanced Techniques in Environmental Biotechnology: Addressing Global Challenges - V. Sailaja (AG Volumes, 2025)
Ecological biotechnology is a contemporary method of environmental protection and preservation that effectively integrates the advancements of microbiology, biochemistry, genetic engineering, and chemical technologies. This article surveys the diverse literature on the challenges and advancements in environmental biotechnology. It concluded that, biotechnology is revolutionizing environmental sustainability by offering innovative solutions to global challenges through advanced waste processing, agricultural enhancements, and the creation of sustainable industrial cycles. Its expanding role in everyday life and economic development highlights its transformative potential. Despite ongoing ethical, legal, and environmental concerns, extensive research supports the safe and beneficial use of biotechnological innovations, such as GM crops. Continued progress in this field requires responsible development, balancing scientific advancement with societal and ecological considerations to ensure a sustainable future for all.